Characterization of polyphenol oxidase in ginger (Zingiber officinale R.) - Panicker R Pournami, Joseph Ancy, B Thayumanavan, (Journal of Spices and Aromatic Crops, 2012)
A polyphenol oxidase (PPO) isoform that showed expression at all developmental stages of rhizomes in 13 ginger (Zingiber officinale R.) accessions and the only one observed at full maturity of rhizome was characterized. The isoform is a non-covalent homo-dimeric protein of 66 kDa subunits. The native molecular mass was estimated at 127 kDa using non- reducing SDS–PAGE (10%). Its activity after purification was confirmed by substrate staining both in native gel (7%) and non-reducing SDS gel (10%). The N-terminal amino acid sequence of the subunit of ginger rhizome polyphenol oxidase is ‘Glu-Gln-Gly-Val-Gly-Gly-Asp-Asp-Gly-Leu-.’ The enzyme showed maximum activity at pH 4.5 and 60°C. The PPO is thermo-tolerant and active in a broad pH range (pH 3.5 to 8). Heat inactivation studies showed a decrease in enzyme activity at 75°C and above. Lower concentrations of MgCl2 (1 mM) and CaCl2 (0.5 mM) activated the enzyme whereas higher concentrations (10 mM) reduced the activity. L- Cysteine HCl, L-ascorbic acid, potassium metabisulfite and NaCl inhibited PPO strongly. Western blot analysis of crude leaf extracts with polyclonal antiserum raised against purified PPO confirmed absence of its expression in leaves at different stages of development. Polyclonal anti-PPO antiserum cross reacted with Solanum tuberosum, Raphanus sativus and Dioscorea esculenta tuber extracts and Solanum melongena, Malus sylvestris and Musa paradisiaca fruit extracts but no cross reactivity was observed with Curcuma amada and Ipomoea batatas extracts.